2017
DOI: 10.1080/00498254.2017.1346333
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, metabolism and excretion of [14C]omarigliptin, a once-weekly DPP-4 inhibitor, in humans

Abstract: 1. Omarigliptin (MARIZEV®) is a once-weekly DPP-4 inhibitor approved in Japan for the treatment of type 2 diabetes. The objective of this study was to investigate the absorption, metabolism and excretion of omarigliptin in humans. 2. Six healthy subjects received a single oral dose of 25 mg (2.1 μCi) [C]omarigliptin. Blood, plasma, urine and fecal samples were collected at various intervals for up to 20 days post-dose. Radioactivity levels in excreta and plasma/blood samples were determined by accelerator mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…The DPP-4 inhibitors differ widely in their chemistry and pharmacokinetic properties [34] (Table 2). Some have intrinsically long-half-lives (alogliptin, evogliptin, gemigliptin, linagliptin, omarigliptin, sitagliptin, teneligliptin and trelagliptin) [34][35][36][37][38][39], giving sustained DPP-4 inhibition which allows once-daily or, for omarigliptin and trelagliptin, once-weekly dosing. Others have much shorter half-lives (anagliptin, saxagliptin and vildagliptin) [34,40]; however, whereas the aforementioned inhibitors interact non-covalently with the enzyme, the cyanopyrrolide moiety in anagliptin, saxagliptin and vildagliptin promotes covalent binding, resulting in these inhibitors remaining bound to the enzyme for longer than predicted from their short half-lives [41,42].…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DPP-4 inhibitors differ widely in their chemistry and pharmacokinetic properties [34] (Table 2). Some have intrinsically long-half-lives (alogliptin, evogliptin, gemigliptin, linagliptin, omarigliptin, sitagliptin, teneligliptin and trelagliptin) [34][35][36][37][38][39], giving sustained DPP-4 inhibition which allows once-daily or, for omarigliptin and trelagliptin, once-weekly dosing. Others have much shorter half-lives (anagliptin, saxagliptin and vildagliptin) [34,40]; however, whereas the aforementioned inhibitors interact non-covalently with the enzyme, the cyanopyrrolide moiety in anagliptin, saxagliptin and vildagliptin promotes covalent binding, resulting in these inhibitors remaining bound to the enzyme for longer than predicted from their short half-lives [41,42].…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…The DPP-4 inhibitors also differ in their elimination pathways (Table 2), which can influence their clinical usage. Alogliptin, linagliptin, omarigliptin, sitagliptin and trelagliptin are not appreciably metabolized, and are eliminated predominantly unchanged [34,37,39]. Gemigliptin undergoes modest hepatic metabolism to form an active metabolite which makes up ∼10% of the circulating material but which is twice as potent as the parent inhibitor [36,44].…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that DPP4 secreted by hepatocytes in obese mice promotes adipose inflammation and insulin resistance [14]. Omarigliptin is a DPP4 inhibitor with a half-life that enables weekly dosing and it has a wide organ distribution including the liver [1,15]. Therefore, it might decrease morning glucagon levels more effectively than daily DPP4 inhibitors [16].…”
Section: Discussionmentioning
confidence: 99%
“…Omarigliptin is a potent, selective, oral dipeptidyl peptidase 4 (DPP4) inhibitor with a half-life that allows weekly dosing [1,2]. Because they can ameliorate glycemic control in patients with type 2 diabetes without severe side effects, daily DPP-4 inhibitors have become an established part of the treatment regimens for patients over the past 10 years.…”
Section: Introductionmentioning
confidence: 99%